Zhodnocení finanční situace podniku a návrhy na její zlepšení - Skuhravý, Kevin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Tato diplomová práce se zabývá tématem zhodnocení finanční situace společnosti Tesla Inc. a návrhů jejího zlepšení. Na základě teoretických poznatků je provedena strategická a finanční analýza, z nichž poté vychází jednotlivé návrhy na zlepšení finanční situace podniku.

This diploma thesis deals with the topic of evaluating the financial situation of Tesla Inc. and suggestions for its improvement. Based on the theoretical knowledge, a strategic and financial analysis is performed, which then leads to individual proposals for improving the financial situation of the company.
Evaluation of the Financial Situation of the Company and Proposals for its Improvement
Keywords: Finanční analýza; strategická analýza; absolutní ukazatele; rozdílové ukazatele; poměrové ukazatele; SWOT; McKinsey; Porter; Financial analysis; strategic analysis; absolute indicators; difference indicators; ratio indicators; SWOT; McKinsey; Porter